2018
DOI: 10.1002/zaac.201800267
|View full text |Cite
|
Sign up to set email alerts
|

On the Demystification of “HPbI3” and the Peculiarities of the Non‐innocent Solvents H2O and DMF

Abstract: Detailed investigations by XRD reveal that the precursor “HPbI3” that was obtained by reaction of aq. conc. hydroiodic acid HI and PbI2 in DMF is (CH3)2NH2PbI3. (CH3)2NH2+ is formed by solvent reaction as already described in the literature but not properly assigned. Attempts to synthesize HPbI3 by gas phase reaction of PbI2 with aq. conc. HI yielded light‐yellow crystals of the oxonium salt H18O8Pb3I8 (Pbam, Z = 2, a = 10.075, b = 30.162, c = 4.5664 Å). The crystal structure of H18O8Pb3I8 consists of trimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 40 publications
7
39
1
Order By: Relevance
“…We synthesized the DMAPbI 3 powder following the commonly used method by reacting PbI 2 and HI in DMF (details in Methods section), which is used as the starting material for making the Cs-based perovskite films (Figure 1A). This method was once widely believed to produce the “mythical” HPbI 3 (Wang et al., 2015, Pang et al., 2016, Long et al., 2016), whereas a recent study challenged such claim and proposed that the product would be DMAPbI 3 (Ke et al., 2018, Daub and Hillebrecht, 2018), which is now confirmed, finally, by our detailed analysis as described below.
Figure 1Synthesis and Characterization of the DMAPbI 3 Powder(A) Schematic diagram for synthesizing DMAPbI 3 powder.(B) XRD pattern of the DMAPbI 3 powder.(C and D) SEM images of the DMAPbI 3 powder with different resolutions, See also Figure S1.(E–H) Energy-dispersive spectrometric (EDS) mapping for N, Pb, and I elements in the DMAPbI 3 powder: EDS mapping of (E) N, Pb, and I elements overlay, (F) N element, (G) Pb element, and (H) I element distribution of the DMAPbI 3 powder.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized the DMAPbI 3 powder following the commonly used method by reacting PbI 2 and HI in DMF (details in Methods section), which is used as the starting material for making the Cs-based perovskite films (Figure 1A). This method was once widely believed to produce the “mythical” HPbI 3 (Wang et al., 2015, Pang et al., 2016, Long et al., 2016), whereas a recent study challenged such claim and proposed that the product would be DMAPbI 3 (Ke et al., 2018, Daub and Hillebrecht, 2018), which is now confirmed, finally, by our detailed analysis as described below.
Figure 1Synthesis and Characterization of the DMAPbI 3 Powder(A) Schematic diagram for synthesizing DMAPbI 3 powder.(B) XRD pattern of the DMAPbI 3 powder.(C and D) SEM images of the DMAPbI 3 powder with different resolutions, See also Figure S1.(E–H) Energy-dispersive spectrometric (EDS) mapping for N, Pb, and I elements in the DMAPbI 3 powder: EDS mapping of (E) N, Pb, and I elements overlay, (F) N element, (G) Pb element, and (H) I element distribution of the DMAPbI 3 powder.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has recently been suggested that the “mythical” hydrogen lead trihalide (HPbI 3 , also known as PbI 2 ∙ x HI), the often-assumed reaction product of HI and PbI 2 , does not actually exist (Ke et al., 2018). Instead, adding acid to DMF is known to generate a weak base dimethylamine (DMA) through hydrolysis (Noel et al., 2017, Sutherland, 2017, Daub and Hillebrecht, 2018), and with the presence of PbI 2 the actual final product is believed to be a compound of DMAPbI 3 (DMA + = dimethylammonium, (CH 3 ) 2 NH 2 + ). Despite the broad adoption of such reaction route in fabricating Cs-based perovskite materials, systematic investigation of DMAPbI 3 as the starting material and its effect on the performance of the resultant PSCs has been largely missing, breeding continued debates and confusion.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, inorganic perovskites are still hybrid organic‐inorganic perovskites . Here, HI acts with PbI 2 containing DMF to remove H 2 O, PbO, and PbO 2 in PbI 2 and also eventually form dimethylammonium (DMA + ) group . Similarly, Liu and coworkers reported hydrolysis‐derived materials (i.e., DMAPbI 3 ) and analyzed its role in producing high‐quality PSCs in detail by changing the ratio of CsI/DMAPbI 3 in the precursor .…”
Section: Tga Parameters Of Different Syn‐pbi2 Powders (Extracted Frommentioning
confidence: 99%
“…In the presence of dissolved PbI 2 and excessive iodide anions, the main product of this reaction, dimethylammonium (DMA + ), forms a solid phase DMAPbI 3 , which was previously mistaken for the mythical "HPbI 3 " [12,13]. Forming non-perovskite phase, the DMA affects the properties of the resulting perovskite film [11,13,14] (for more detailed discussion see SI). However, even a more significant problem of using DMF-based acid solutions is almost uncontrollable changing of solution composition upon preparation, storage, and processing.…”
Section: Introductionmentioning
confidence: 99%